Updates in Congenital Heart Disease: Can Outcomes Improve? - Martin, Gerard R.; Cross, Russell R.; Hom, Lisa A.; Klugman, Darren (American Journal of Perinatology, 2019)
Despite numerous advances in medical and surgical management, congenital heart disease (CHD) remains the number one cause of death in the first year of life from congenital malformations. The current strategies used to approach improving outcomes in CHD are varied. This article will discuss the recent impact of pulse oximetry screening for critical CHD, describe the contributions of advanced cardiac imaging in the neonate with CHD, and highlight the growing importance of quality improvement and safety programs in the cardiac intensive care unit.
Keywords: congenital heart disease; quality improvement; pulse oximetry screening